Одиночество Мага: посвящается сестре / [иллюстрации Лео Хао] - Перумов Николай Даниилович (2001)
Экземпляры: абонем (20180622) / Инвентарный номер: / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 27 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6